Water immersion cooling of high power density electronics. (February 2020) - Birbarah, Patrick; Gebrael, Tarek; Foulkes, Thomas; Stillwell, Andrew; Moore, Alexandra; Pilawa-Podgurski, Robert; Miljkovic, Nenad
Graphical abstract: Highlights: First experimental demonstration of immersion cooling of electronics in water. Heat fluxes up to 562 W/cm 2 demonstrated in water. Experimental comparison of water, water-glycol mixture, and dielectric fluids for immersion cooling. Investigation of device level thermal performance for different Gallium Nitride transistors for power electronics. Abstract: Thermal management of power electronic systems is a key bottleneck to power densification. Single phase cooling is limited to low heat transfer coefficients (<2 kW/(m 2  K)) while two-phase cooling such as flow boiling suffers from hydrodynamic instabilities. Immersion cooling has emerged as a potential solution to overcome these barriers by enabling the boiling of a cooling fluid directly from electronic components, thereby removing thermal interface materials and packaging constraints encountered in the aforementioned approaches. State-of-the-art (SOA) immersion cooling systems utilize dielectric heat transfer liquids due to electrical considerations, which presents fundamental disadvantages related to the relatively low boiling point, low critical heat flux (<20 W/cm 2 ), and relatively poor thermophysical properties such as thermal conductivity, latent heat, and surface tension, when compared to higher performance fluids such as water. In this study, we propose an approach that uses immersion cooling directly in water. We use the electrically insulating nature of Parylene C coatings to insulate the printed circuit board (PCB) and electronic devices from the water. We demonstrate experimentally the effectiveness of conformal layers of Parylene C as thin as 1  μ m in preventing current from leaking between the electronic components and the surrounding water when the system is subjected to voltages up to 200 Volts. Furthermore, we provide the heat flux and convection heat transfer coefficient obtained in 3 M Novec 72DE and 7300 dielectric fluids, water, and a 50/50 in volume mixture of water and ethylene glycol (WEG) as a function of hot-spot-to-fluid temperature difference in both natural convection and nucleate pool boiling regimes. Gallium Nitride (GaN) transistors with different board-mounting techniques and thermal pad locations are used as heat sources. Heat fluxes up to 562 W/cm 2 are measured in water. As a proof of concept, water immersion cooling is tested successfully on a 2 kW power converter operating at 97.2% efficiency in deionized water. This study not only demonstrates immersion cooling in water of high-power density electronics, but also develops design guidelines for cooling of electronic components through the use of novel electrically insulating coatings coupled with attractive electrically conducting cooling media.